Developement And Evaluation Of A Nasba System For The Diagnosis Of Cholera Using Elisa And Biosensor Methods - Su Yin, Lee (2008)
Taun (kolera) ialah penyakit ciri-birit yang disebabkan Vibrio cholerae.